2021
DOI: 10.3390/catal11121553
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Influence of Key Preparation Parameters on the Performance of MoS2/Graphene Oxide Composites as Active Materials in Supercapacitors

Abstract: Advances in energy storage and energy conversion play an essential role nowadays because the energy demands are becoming greater than ever. To overcome the actual performances of the materials used to build supercapacitors, a combination of transition metal dichalcogenides (TMDCs) and graphene oxide (GO) or reduced graphene oxide (rGO) as graphene-based structures are often studied for their excellent properties, such as high specific area and good electrical conductivity. Nevertheless, synthesis pathways and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 81 publications
(158 reference statements)
0
2
0
Order By: Relevance
“…The main advantage of the lithium intercalation method is the access to the metal phase 1T, which is created by transferring the load from Li to MoS 2 . The 2H to 1T atomic structure rearrangements in this method occur [75].…”
Section: Lithium Intercalationmentioning
confidence: 99%
“…The main advantage of the lithium intercalation method is the access to the metal phase 1T, which is created by transferring the load from Li to MoS 2 . The 2H to 1T atomic structure rearrangements in this method occur [75].…”
Section: Lithium Intercalationmentioning
confidence: 99%
“…Previous studies reported the nanoscale TMDCs exhibit unique characteristics such as enhancement of photoluminescence [20,21], high hole mobility [22], and high capacitance [23]. They have been proposed for optoelectronic devices [24][25] and hole transport layer in solar cells [26].Furthermore the sub micrometer TMDCc particles also show interesting features such as high flexibility and conductivity [27,28], high current density [29], and adjustable light emission [30] which open for applications in submicrometer thin antennas [27], sub-micrometer channel of field effect transistor [28 ], supercapacitor electrode [29], and light source [30].…”
Section: Introductionmentioning
confidence: 99%